2018
DOI: 10.1155/2018/6745629
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Aboveground Biomass on Private Forest Using Sentinel-2 Imagery

Abstract: Private forests have a crucial role in maintaining the functioning of the Indonesian forest ecosystem especially because of the continuous degradation of natural forests. Private forests are a part of social forestry which becomes a tool for the Indonesian government to reduce carbon dioxide (CO2) emission by 26% by 2030. The United Nations Programme on Reducing Emissions from Deforestation and Forest Degradation has encouraged the Indonesian government to establish a forest monitoring system by estimating for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 51 publications
2
16
1
4
Order By: Relevance
“…The fact that all analysed services are evaluated as dependent on plant production, i.e., the amount and condition of biomass produced, also speaks for this direction of expansion. This is also a key feature for the necessary remote sensing methods (spectral analyses and vegetation indices) [52,53]. Algorithms for determining vegetation indices, which can be used to assess the health of vegetation, are well known today, and are optimized for different types of multispectral data (Landsat, Sentinel .…”
Section: Discussionmentioning
confidence: 99%
“…The fact that all analysed services are evaluated as dependent on plant production, i.e., the amount and condition of biomass produced, also speaks for this direction of expansion. This is also a key feature for the necessary remote sensing methods (spectral analyses and vegetation indices) [52,53]. Algorithms for determining vegetation indices, which can be used to assess the health of vegetation, are well known today, and are optimized for different types of multispectral data (Landsat, Sentinel .…”
Section: Discussionmentioning
confidence: 99%
“…The nonparametric models include regression k-nearest neighbor [88][89][90], artificial neural network [91], regression tree [35,92,93], random forest [18,[94][95][96], support vector machine [94], and maximum entropy [97]. These functions have been developed with satellite imagery of low [98][99][100], medium [100][101][102][103], and high [73,[75][76][77][104][105][106] spatial resolution. In the fifth approach, biomass is modeled with data from Synthetic Aperture Radar (SAR) with bagging stochastic gradient boosting algorithms, backscattering amplitudes, and multivariate linear regression [107][108][109].…”
Section: Biomass Estimationmentioning
confidence: 99%
“…Research related to biomass and carbon storage of community forests in Gunungkidul District has been carried out by scholars (Askar et al 2018;Indrajaya and Sudomo, 2016;Purwanto et al 2012;Sulistyo et al 2010). However, research on similar themes that focused specifically on wono is rarely found.…”
Section: Introductionmentioning
confidence: 99%